EFFECT OF SCHOOL ENVIRONMENT ON THE PERSONALITY TRAITS OF CLASS 10TH STUDENTS (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
A Persons environment consists of sum of the sum total of stimulation, which he receives from the time of his conception till death.Environemnt consists of physical, intellectual, social, moral, economic, political and cultural forces. All these forces do exert their influence in moulding the personality and behavior of the child.